Про анкерування поздовжньої розтягнутої арматури у залізобетонних балках без попереднього напруження - Максимович, С. Б.; Крочак, О. В.; Maksymovych, S.; Krochak, O. (Видавництво Львівської політехніки, 2018)
Експериментальні дослідження покзали, що навіть у разі дотримання вимог чинних норм про довжину анкерування поздовжньої арматури балки руйнуються від втрати зчеплення поздовжньої арматури з бетоном, не досягнувши міцності похилого перерізу. Висмикування поздовжньої арматури на опорах внаслідок розтріскування бетону і порушення зчеплення потрібно розглядати як недолік конструювання опорної частини. Такі балки не коректно брати до уваги під час проведення аналізу несучої здатності похилих перерізів, тому що анкерування є окремою проблемою у теорії залізобетону. Особливістю згинаних залізобетонних елементів є те, що за дії навантаження епюра розтягуючого зусилля у поздовжній арматурі не відповідає епюрі згинальних моментів внаслідок часткової втрати зчеплення арматури з бетоном після утворення вертикальних тріщин, які допускаються нормами за експлуатаційних навантажень. Для вирішення цієї проблеми пропонують використовувати поняття “правило зміщення розтягуючого зусилля”, яке подано в чинних нормах [1] і Eurocode 2 EN 1992-1-1:2004 [2] для визначення місця обриву поздовжньої арматури в прольоті. Пропонуємо дещо інший підхід, який ґрунтується на зміщенні не розтягуючого зусилля, а зміщенні епюри згинальних моментів. Цей метод вперше запропонував Л. О. Дорошкевич для розра- хунку поперечної арматури. Невідповідність зміни розтягуючого зусилля в поздовжній арматурі і епюри згинальних моментів враховується коефіцієнтом зміщення епюри моментів v , який визначають за допомогою розроблених номограм. Наведено приклад розрахунку довжини анкерування поздовжньої арматури пропонованим методом.

The character of oblique cracking is significantly influenced by the method and reliability of anchoring of the longitudinal tensile reinforcement on the hinge support beams. In many experimental researches the lack of anchoring caused the premature destruction of beams along the sloping cracks. Nevertheless, such destruction of a beam along the sloping crack, at the violation of anchoring on the hinge support, should not be referred to the type of destruction under the influence of internal efforts, caused by the external loading. Pulling out of longitudinal bars of reinforced concrete beams on support, as a result of concrete cracking and adhesion violation, should be considered as a drawback of the supporting part constructing. It is incorrect to take such beams into consideration at doing the analysis of the bearing capacity of sloping cuts, because anchoring is a separate issue in the theory of reinforced concrete studies. The experimental research has shown that even by maintaining standards of current design norms concerning the length of anchoring of the longitudinal reinforcement beams are ruined because of the lack of adhesion of the longitudinal reinforcement with concrete without achieving the strength of the sloping cut. The peculiarity of the bending reinforced concrete elements is the fact that at loading effect the diagram of the stretching effort in the longitudinal reinforcement does not correspond to the diagram of the bending moments as a result of the partial loss of the reinforcement adhesion with concrete after the creation of vertical cracks, which are allowed by design norms at the exploitation loadings. To solve this problem it is suggested to use the notion of “the rule of strengthening of the stretching effort”, available in current design norms [1] and Eurocode 2 EN 1992-1-1:2004 [2] for determining the place of break in the span. We suggest quite a different approach which is based not on the displacement of stretching effort, but on the displacement of the diagram of bending moments. This method was suggested by L. O. Doroshkevych for the calculation of the shear reinforcement. The discrepancy of the stretching effort change in the longitudinal reinforcement and the diagram of bending moments is taken into account by the coefficient of diagram of moments displacement which is determined with the help of developed nomograms. The article presents the example of calculation of the anchoring length of the longitudinal reinforcement by the suggested method.
On anchoring of the longitudinal tensile reinforcement in reinforced concrete beams without pre-stressing
Keywords: анкерування поздовжньої арматури; залізобетонні балки; міцність похилих перерізів; коефіцієнт зміщення епюри моментів; приріст згинального моменту; anchoring of the longitudinal reinforcement; reinforced concrete beams; oblique planes; displacement coefficient of bending moment diagram; bending moment’ increment; 624.012.45.044